2018
DOI: 10.1016/j.ebiom.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

CHAF1A interacts with TCF4 to promote gastric carcinogenesis via upregulation of c-MYC and CCND1 expression

Abstract: BackgroundHistones chaperones have been found to play critical roles in tumor development and progression. However, the role of histone chaperone CHAF1A in gastric carcinogenesis and its underlying mechanisms remain elusive.MethodsCHAF1A expression in gastric cancer (GC) was analyzed in GEO datasets and clinical specimens. CHAF1A knockdown and overexpression were used to explore its functions in gastric cancer cells. The regulation and potential molecular mechanism of CHAF1A expression in gastric cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 46 publications
2
38
1
Order By: Relevance
“…Chromatin assembly factor 1 subunit A (CHAF1A) is a pro-oncogene that plays a role in a variety of tumors, such as colon cancer (Wu et al, 2014), glioblastoma (Peng et al, 2016), ovarian cancer (Xia et al, 2017) and gastric cancer (Zheng et al, 2018). In addition, studies showed that the expression of CHAF1A was increased in cervical cancer and was positively correlated with tumor malignancy (Luo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin assembly factor 1 subunit A (CHAF1A) is a pro-oncogene that plays a role in a variety of tumors, such as colon cancer (Wu et al, 2014), glioblastoma (Peng et al, 2016), ovarian cancer (Xia et al, 2017) and gastric cancer (Zheng et al, 2018). In addition, studies showed that the expression of CHAF1A was increased in cervical cancer and was positively correlated with tumor malignancy (Luo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] CHAF1A was found overexpressed in gastric cancer cell lines and tissue samples and its high expression was predictive of poor outcome. 35 Functional in vitro studies demonstrated that CHAF1A expression promoted gastric cancer cell proliferation by enhancing transcriptional activation of c-MYC and CCND1 genes, through direct binding to their promoter regions. This activation was achieved in concert with TCF4, a mediator of Wnt signalling pathway, suggesting that CHAF1A may act as a co-activator of this important pathway.…”
Section: Discussionmentioning
confidence: 99%
“…CCND1 overexpression has typically been observed to occur in MM precursors with chromosomal 11 and 14 translocations (Miura et al, 2003; Zhan et al, 2006). In gastric cancer, CCND1 has been shown to directly interact with TCF4 through the Wnt signaling pathway (Zheng et al, 2018), suggesting that other mechanisms of CCND1 overexpression may also occur in MM.…”
Section: Discussionmentioning
confidence: 99%